Efficacy of laparoscopic cardiectomy combined with side overlap anastomosis for the treatment of terminal achalasia - Jing-Tao Wang; Yu-Xiang Sun; Rui-Xin Li; Yun-Fei Zhang; Heng-Xuan Ding; Guo-Jun Wang; Bu-Lang Gao (Scientific Reports)
Abstract To investigate the safety and short-term effectiveness of laparoscopic-assisted cardiectomy with side-overlap esophagogastric reconstruction for the treatment of terminal or end-stage achalasia, patients with end-stage achalasia treated with laparoscopic-assisted cardiectomy with side-overlap esophagogastric reconstruction were retrospectively enrolled. The clinical data, surgical data and follow-up were analyzed. Among twenty-five patients enrolled, the achalasia type St was present in 12 (48%) patients, type Sg in 9 (36%), and type aSg in 4 (16%). The surgical time ranged 60–180 min (median 100 min) with an intraoperative blood loss 20-200 ml (median 50 ml). Five (20%) patients experienced complications within a week after surgery, with fever (> 38.5 ℃) in two (40%) patients within 3 days after surgery, abdominal incision infection in one (20%), and anastomotic leak in two (40%). The postoperative hospitalization time ranged 8–44 (median 10) days. Follow-up was conducted 6–38 months (median 16) after surgery. Compared with the preoperative Eckardt score (7.64 ± 1.32), the Eckardt score was significantly (P < 0.01) decreased at one month (0.52 ± 0.87), 6 (0.84 ± 1.11) and 12 (1.23 ± 1.23) months after surgery in all patients. The Eckardt score in type St was significantly (P < 0.05) smaller than in type Sg or aSg at 6 and 12 months after surgery. Seven patients maintained an Eckardt score 0 with complete relief of their symptoms. The effective rate was 100% for type St, 88.8% for type Sg, and 75% for type aSg. The effective rates at 1 month, 6 and 12 months after surgery were 100% (95% CI: 100% -100%), 96% (95% CI: 87.7 -100%), and 92% (95% CI: 80.6 -100%). Two patients were diagnosed with gastroesophageal reflux disease (GERD) at the end of the follow-up. The cumulative incidence of GERD at 1 month, 6 and 12 months after surgery was 0, 4% (95% confidence interval or CI: 0-12.3%), and 8% (95% CI: 0-19.4%). In conclusion, the laparoscopic-assisted cardiectomy with side-overlap esophagogastric reconstruction is safe and effective for the treatment of end-stage achalasia, and the effect is significantly better for achalasia type St than for types Sg and aSg.